الحماية القانونية لأسري الحرب و دور اللجنة الدولية للصليب الاحمر في حمايته (Revue El-Wahat pour les Recherches et les Etudes, 2021)
International Humanitarian Law Is The Guardian Of The Rights Of The Individual During International And Non-International Armed Conflicts. The Prisoner Is Considered The Weakest Link In The Armed Conflict And Requires The Disarming Of The Weapon. The International Community Has Therefore Given Due Legal Protection Through The International Conventions Of The Hague Convention Of 1907 And The Geneva Conventions Of 1929 And Geneva 1949, The First Additional Protocol Of 1977, The Most Important Rights Guaranteed To The Prisoner Through The Period Of Captivity, And The ICRC's Efforts To Protect And Assist The Prisoners In Communicating And Limiting Missing Persons By Developing The Family Information Center As Well As Family Reunification And The Monitoring And Preventive Work It Does For The Captive Key Words-* Prisoners * Legal Protection Of The Prisoner * The Third Geneva Convention Of 1949 * International Committee Of The Red Cross And Red Crescent.